Benzylation of benzene and other aromatics by benzyl chloride over mesoporous AlSBA-15 catalysts - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hartmann, Martin; Halligudi, Shivappa B. (Microporous and Mesoporous Materials, 2005)
Aluminum-containing mesoporous molecular sieves AISBA-15 with different n(Si)/n(Al), ratios and AIMCM-41 have been synthesized hydrothermally and characterized in detail by physicochemical methods, viz. XRD, N(2) adsorption and (27)Al NMR spectroscopy. The low angle XRD and N2 adsorption measurements reveal that the structural order of SBA-15 was retained after the incorporation of Al. The increase of the unit cell parameter with increasing aluminum content and (27)Al MAS NMR spectroscopy confirm the incorporation of aluminum in the framework. Benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over AISBA-15 and AIMCM-41 have been investigated. The influence of various reaction parameters such as reaction temperature, reactant feed ratio and catalyst amount affecting the activity and selectivity of AISBA-15, have been studied. Among the mesoporous catalysts studied, AISBA-15(45), where the number in parentheses indicates the molar nsilnA, ratio, shows both high conversion and high selectivity for the benzylation of benzene. The activity of this catalyst for the benzylation of different aromatic compounds is in the following order: benzene > toluene > p-xylene > mesitylene > anisole. Kinetics of the benzene benzylation over different catalysts have also been investigated. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Alkylation; AlSBA-15; Benzylation; SBA-15

Direct synthesis of well-ordered and unusually reactive FeSBA-15 mesoporous molecular sieves - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hossain, K. Z.; Halligudi, Shivappa B.; Hartmann, Martin; Nomura, M. (Chemistry of Materials, 2005)
Large-pore hexagonal SBA-15 molecular sieves partially substituted with iron(III) have been synthesized for the first time in highly acidic media. The degree of iron(III) incorporation into SBA-15 can easily be controlled by a simple adjustment of the molar ratio of water and hydrochloric acid. All the materials have been characterized by XRD, N-2 adsorption, UV-Vis DRS, ESR, and XANES spectroscopy. The characterization of the FeSBA-15 materials by UV-Vis DRS, ESR, and XANES spectroscopies suggests that the iron atoms are highly dispersed and mostly occupy isolated tetrahedral sites. XANES studies revealed that the proportion of tetrahedrally coordinated Fe atoms decreases with decreasing n(Si)/n(Fc) ratios. Benzylation of benzene (or substituted benzenes) using benzyl chloride as the alkylating agent over FeSBA-15 with different n(Si)/n(Fe) ratios was investigated as was the same reaction using AISBA-15 as catalyst. The influence of parameters such as reaction temperature, reactant feed ratio, and the presence of electron-donating substituents on the activity and selectivity of AISBA-15 was studied. Under optimized reaction conditions, the FeSBA-15 catalyst showed a superior catalytic performance in the benzylation of benzene and other aromatics using benzyl chloride, with a clean conversion of benzyl chloride to the monoalkylated product (100% selectivity) with a very high rate constant when compared to other mesoporous materials such as AISBA-15 and FeHMS. Interestingly, use of FeSBA-15(21) resulted in quantitative conversion of benzyl chloride with a high rate constant of 2420.5 x 10(-4) min(-1) under the optimized reaction conditions.

Formation of nanosized zirconia-supported 12-tungstophosphoric acid in mesoporous silica SBA-15: a stable and versatile solid acid catalyst for benzylation of phenol - Sawant, D. P.; Vinu, A.; Jacob, Nalini E.; Lefebvre, F.; Halligudi, Shivappa B. (Journal of Catalysis, 2005)
A nanosized zirconia-supported 12-tungstophosphoric acid (TPA) in SBA-15 composite was prepared by wet impregnation of TPA/ZrO2 nanoparticles inside the mesoporous channels of SBA-15. The resulting composite material was calcined at 1123 K and characterized by elemental analysis, powder X-ray diffraction, nitrogen adsorption isotherms, transmission electron microscopy (TEM), scanning electron microscopy (SEM), solid-state P-31 CP-MAS NMR, Si-29 MAS NMR, UV-vis diffuse reflectance spectra, FTIR, TPD of ammonia, FTIR pyridine adsorption, and thermogravimetric analysis (TG-DTG). The synthesized TPA/ZrO2/SBA-15 showed a well-ordered hexagonal inesoporous structure and mesoporous support SBA-15 stabilized ZrO2-t (tetragonal) phase with crystal size in the range of 3-4 nm. SBA-15 was a better support than MCM-41 and MCM-48 because it retained its mesostructure even after high TPA loading and high calcination temperatures. Mesoporous silica support plays an important role in stabilizing the catalytically active tetragonal phase of zirconia, which gave the most active catalysts. The catalysts were examined for their catalytic activities in the liquid phase benzylation of phenol with benzyl alcohol and the catalyst 15 wt% TPA/ 22.4 wt% ZrO2/SBA-15 calcined at 1123 K was found to have high acidity and to be 10 times more active than neat TPA/ZrO2 Under the reaction conditions studied in benzylation of phenol. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: nanosized; phenol benzylation reaction; terragonal phase; TPA/ZrO2

Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Tungstophosphoric acid supported over zirconia in mesoporous channels of MCM-41 as catalyst in veratrole acetylation - Sawant, Dhanashri P.; Vinu, A.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 were synthesized and tested for their catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5-50 wt.%) on 22.4 wt.%ZrO2/MCM-41 and 15 wt.%TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. The physico-chemical characterization of the supported catalysts was done by powder X-ray diffraction (XRD), surface area measurement (BET), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed-infrared (FT-IR) spectroscopy, UV-vis diffuse reflectance spectra, Temperature programmed desorption (TPD) of ammonia, FT-IR pyridine adsorption and (31) P cross polarization-magic angle spinning (CP-MAS) NMR spectroscopy. The mesoporous silica supports play an important role in stabilizing catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/MCM-41 calcined at 1123 K was found to have highest acidity and at least four times more active than neat 15 wt.%TPA/ZrO2 in veratrole acetylation to acetoveratrone by acetic anhydride. Reaction conditions were evaluated with 15 wt.%TPA/22.4 wt:%ZrO2/MCM-41 calcined at 1123 K to get higher conversion of acetic anhydride to acetoveratrone. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) TPA into the medium under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acetoveratrone; acetylation; MCM-41; TPA/ZrO2; veratrole

Alkene epoxidation catalyzed by vanadomolybdophosphoric acids supported on hydrated titania - Ingle, Rohit H.; Vinu, A.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Vanadomolybdophosphoric acids wet-impregnated oil hydrated titania (TiO(2) - xH(2)O), make ail efficient catalytic system for the epoxidation of a variety of alkenes with organic solvent extracted TBHP as the oxidant. By,in appropriate choice of solvent, the catalyst call be reused at least three times without much loss in the activity for subsequent runs. XRD shows that the heteropoly acid is uniformly dispersed over the support and up to 15 wt% loading of the heteropoly acid, no additional peak of the same call be seen in the XRD pattern of the catalyst. The reactivity varied with the nature of alkene but the major product was always the corresponding epoxide. The catalytic system is free of high temperature calcination steps and tedious multi-step procedures, normally encountered in the heter-ogenization of heteropoly acids. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkenes; epoxidation; heteropoly acids; TBHP; titania; vanadomolybdophosphoric acids

Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol